Impaired Activity of Ryanodine Receptors Contributes to Calcium Mishandling in Cardiomyocytes of Metabolic Syndrome Rats - Fernández-Miranda, Gaudencio; Romero-Garcia, Tatiana; Barrera-Lechuga, Tarín P.; Mercado-Morales, Martha; Rueda, Angélica (Frontiers in Physiology, 2019)
Metabolic syndrome (MetS) has become a global epidemic. MetS is a serious health problem because of its related cardiovascular complications, which include hypertension and delayed heart rate recovery after exercise. The molecular bases of cardiac dysfunction in MetS are still under scrutiny and may be related to anomalies in the activity and expression of key proteins involved in the cardiac excitation-contraction coupling (ECC). The cardiac Ca2+ channel/Ryanodine Receptor (RyR2) participates in releasing Ca2+ from internal stores and plays a key role in the modulation of ECC. We examined alterations in expression, phosphorylation status, Ca2+ sensitivity, and in situ function (by measuring Ca2+ sparks and Ca2+ transients) of RyR2; alterations in these characteristics could help to explain the Ca2+ handling disturbances in MetS cardiomyocytes. MetS was induced in rats by adding commercially refined sugar (30% sucrose) to their drinking water for 24 weeks. Cardiomyocytes of MetS rats displayed decreased Ca2+ transient amplitude and cell contractility at all stimulation frequencies. Quiescent MetS cardiomyocytes showed a decrease in Ca2+ spark frequency, amplitude, and spark-mediated Ca2+ leak. The [3H]-ryanodine binding data showed that functionally active RyRs are significantly diminished in MetS heart microsomes; and exhibited rapid Ca2+-induced inactivation. The phosphorylation of corresponding Ser2814 (a preferential target for CaMKII) of the hRyR2 was significantly diminished. RyR2 protein expression and Ser2808 phosphorylation level were both unchanged. Further, we demonstrated that cardiomyocyte Ca2+ mishandling was associated with reduced SERCA pump activity due to decreased Thr17-PLN phosphorylation, suggesting a downregulation of CaMKII in MetS hearts, though the SR Ca2+ load remained unchanged. The reduction in the phosphorylation level of RyR2 at Ser2814 decreases RyR2 availability for activation during ECC. In conclusion, the impaired in situ activity of RyR2 may also account for the poor overall cardiac outcome reported in MetS patients; hence, the SERCA pump and RyR2 are both attractive potential targets for future therapies.